Kata adverba dalam karya Halis Azhan Mohd Hanafiah / Vijaya Letchumi Karuppiah - Vijaya Letchumi, Karuppiah (2016)
The aim of this research is to analyse adverbs which had raised issues in Malay linguistics. Many language researchers have debated and discussed on adverbs in Malay, yet no decision has been reached. Therefore, this study aims to describe the forms and types of adverbs as well as to analyse the position of adverbs in the sentence construction. Data of adverbs for the study were taken from the novel Azfa Hanani written by Halis Azhan Mohd Hanafiah, students edition, 2010. This is a descriptive research, using two approaches, i. e. library research and textual study. Some 303 adverbs were identified from the corpus. Ferdinand de Saussure‟s concept of syntagmatic and paradigmatic relations were used to classify the data. The results show that the data can be classified into four forms of adverbs, i. e. kata adverba jati (natural adverbs), kata adverba asalnya kata adjektif (originally adjective adverbs), kata adverba asalnya kata kerja (originally verb adverbs) and kata adverba gandaan (duplicated adverbs). This research also attempts to classify adverbs into seven types, based on the definision and classification of several prominent linguists, i. e. adverbs of manner, time, place, frequency, emphasis, feeling and uncertainty. The study also uses the tree structure technique which was introduced by Noam Chomsky in the GenerativeTransformation theory to identify the position of adverbs in sentences. It is found that adverbs can be present in the subject, the predicate and parts of the predicate. The study concludes that adverbs can be modifiers to nouns/noun phrases, verbs/verb phrases, adjectives/adjective phrases, prepositional phrases, other adverbs and to the whole sentence, whether in front, behind or simultaneously in front and behind the modified item.